Sessiia verkhovnogo soveta Rossiiskoi Federatsii . Sessiia verkhovnogo soveta Rossiiskoi Federatsii . Session of the Supreme Soviet of the Russian Federation . Сессия Верховного Совета Российской Федерации - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Discussion of the threat of an anti-constitutional state conspiracy. Series description: Broadcast of the sessions of the the Supreme Soviet of the Russian Federation with journalists' comments. Обсуждение угрозы антиконституционного государственного заговора. Описание серии: Трансляция сессий Верховного Совета Российской Федерации с комментариями журналистов.